Pituitary Adenylate Cyclase-Activating Polypeptide: A Potent Therapeutic Agent in Oxidative Stress - Nadia Sadanandan; Blaise Cozene; You Jeong Park; Jeffrey Farooq; Chase Kingsbury; Zhen-Jie Wang; Alexa Moscatello; Madeline Saft; Justin Cho; Bella Gonzales-Portillo; Cesar V. Borlongan (MDPI AG, 2021)
Stroke is a life-threatening condition that is characterized by secondary cell death processes that occur after the initial disruption of blood flow to the brain. The inability of endogenous repair mechanisms to sufficiently support functional recovery in stroke patients and the inadequate treatment options available are cause for concern. The pathology behind oxidative stress in stroke is of particular interest due to its detrimental effects on the brain. The oxidative stress caused by ischemic stroke overwhelms the neutralization capacity of the body's endogenous antioxidant system, which leads to an overproduction of reactive oxygen species (ROS) and reactive nitrogen species (RNS) and eventually results in cell death. The overproduction of ROS compromises the functional and structural integrity of brain tissue. Therefore, it is essential to investigate the mechanisms involved in oxidative stress to help obtain adequate treatment options for stroke. Here, we focus on the latest preclinical research that details the mechanisms behind secondary cell death processes that cause many central nervous system (CNS) disorders, as well as research that relates to how the neuroprotective molecular mechanisms of pituitary adenylate cyclase-activating polypeptides (PACAPs) could make these molecules an ideal candidate for the treatment of stroke.